Study on adverse Effectiveness of Lactic Acid Bacteria against methicillin resistant Staphylococcus aureus - Lertcanawanichakul, Monthon; Pongpanitanon, Pongphan; Akarasut, Suchada (Archives of Allied Health Sciences, 2005)
abtract not available